LATGALIANNESS – THE SECOND, ADDITIONAL OR THE ONLY NATIONAL IDENTITY - Cibuļs, Juris (Via Latgalica, 2012)
The main objective of this article is to stress and to prove that the Latgalian national identity is the only national identity for a lot of citizens of Latvia and it is not the second or the additional identity that may be attributed only to secret service men inter alia.My personal studies of official sources, literature and correspondence with officials of state institutions, etc. are at the basis of this article.National identity is the person’s identity and sense of belonging to one state or to one nation, a feeling one shares with a group of people, regardless of one’s status of citizenship.National identity is not inborn trait; various studies have shown that a person’s national identity is a direct result of the presence of elements from the „common points” in people’s daily lives: national symbols, language, national colours, the nation’s history, national consciousness, culture, music, cuisine, radio, television, etc.There are cases where national identity collides with a person’s civil identity. For example, many Israeli Arabs associate themselves or are associated with the Arab or Palestinian nationality, while at the same time they are citizens of the state of Israel, which is in conflict with the Palestinians and with many Arab countries.There are also cases in which the national identity of a particular group is oppressed by the government in the country where the group lives. A notable example was in Spain under the authoritarian dictatorship of Francisco Franco (1939–1947) who abolished the official statute and recognition for the Basque, Galician, and Catalan languages for the first time in the history of Spain and returned to Spanish (Castillian) as the only official language of the State and education, although millions of citizens of Spain spoke other languages.During the first independence period of Latvia in the thirties, the schools of Latgale used Latgalian as the language of instruction during the first four years, Latgalian language was taught as a subject starting with the third year twice a week. After the coup d’état on May 15, 1934 the Latgalian textbooks were withdrawn from use and even burnt.There is enough evidence to prove that the Latvian nationalist elite was very unwilling to accept the spread of Latgalian both during the first period of independence and the multinational Soviet rule. The positive expression of one’s national identity is patriotism, and the negative is chauvinism.Latgalians are an autochthonous people living mostly in the eastern part of the contemporary Latvia. As regards Latgalian (it has been named in different ways – language, dialect, subdialect, foreign language, but it does not change the essence of the phenomenon) various resolutions, decrees etc. have been passed and adopted.Participants of the 2nd Conference on Latgalistics (Rezekne, October 17, 2009) adopted the resolution „On the Status of a Regional Language to Be Attributable to the Latgalian Language”.In accordance with the new Official Language Law enacted on September 1, 2000 the official language in Latvia is the Latvian language. Section 3 Paragraph 4 of the Law prescribes: „The State shall ensure the maintenance, protection and development of the Latgalian written language as a historic variant of the Latvian language.” However, it is a very formal statement. Strange as it may sound but the Senate of the Supreme Court of the Republic of Latvia has adopted a decision (August 18, 2009, Case No. A42571907 SKA-596/2009): „The Senate concludes that in the first sentence of Article 4 of the Satversme (the Constitution – J. C.) of the Republic of Latvia the concept „The Latvian language” means the Latvian literary language. It is the official language for the purpose of Section 110 of the Administrative Procedure Law. From the conclusion that for the purpose of Section 110 Paragraph I of the Administrative Procedure Law the official language is the Latvian literary language it follows that other subdialects or languages for the purpose of Section 110 Paragraph II of the Administrative Procedure Law are foreign languages and a document drafted in the Latgalian literary language is to be acknowledged as a document drafted in a foreign language. This decision is not to be appealed against.”It took the Latgalian enthusiasts (I am one of them) seven years (2003–2010) to get the individual code for the Latgalian language. ISO 639/Joint Advisory Committee (Library of Congress, Washington) has finally attributed the code, namely, LTG.Hopefully the Latgalian identity will not be swept away and this only identity for a lot of citizens of Latvia will be fought for and preserved also in the shadow of the so-called majority.